2022
DOI: 10.3390/ijerph19063317
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Multimorbidity Patterns over 16 Years in Older Taiwanese People and Their Relationship to Mortality

Abstract: Understanding multimorbidity patterns is important in finding a common etiology and developing prevention strategies. Our aim was to identify the multimorbidity patterns of Taiwanese people aged over 50 years and to explore their relationship with health outcomes. This longitudinal cohort study used data from the Taiwan Longitudinal Study on Aging. The data were obtained from wave 3, and the multimorbidity patterns in 1996, 1999, 2003, 2007, and 2011 were analyzed separately by latent class analysis (LCA). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…We called the four multimorbidity patterns from our previous work, which showed the comorbidity components of each multimorbidity pattern and the consistency through following years. 21 Table 1 shows the demographic and clinical characteristics of the participants with their distinct multimorbidity patterns and frailty status in 1996. The mean age was highest for those in the Arthritis-cataract group with frailty.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We called the four multimorbidity patterns from our previous work, which showed the comorbidity components of each multimorbidity pattern and the consistency through following years. 21 Table 1 shows the demographic and clinical characteristics of the participants with their distinct multimorbidity patterns and frailty status in 1996. The mean age was highest for those in the Arthritis-cataract group with frailty.…”
Section: Resultsmentioning
confidence: 99%
“…Both model fit (lower AIC or BIC values) and interpretability were used to select the most appropriate model. We called the four multimorbidity patterns from our previous work, which showed the comorbidity components of each multimorbidity pattern and the consistency through following years 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that there is a clear geographic concentration in sports technology research on older adults’ technology acceptance models. Ho et al’s research showed that Taiwan became an aging society in 2018, and it is expected that it will become a super-aging society in 2025 [ 38 ]. The aging population is growing rapidly, and health problems will also increase.…”
Section: Discussionmentioning
confidence: 99%
“…These disease combinations could be named the cardio-metabolic pattern, cardio-degenerative pattern, and metabolic-degenerative pattern. It had been established in previous studies that the above multimorbidity pattern had similar risk factors and pathophysiology [ 48 , 49 , 50 ]. It could be hypothesized that if individuals are affected by HTN or DM, they are more likely to accumulate other metabolic or degenerative morbidities, such as high cholesterol, CAD, osteoporosis, etc.…”
Section: Discussionmentioning
confidence: 99%